Degradation of single layer MEH-PPV organic light emitting diode (OLED) - Nurjuliana, Juhari; Wan Haliza, Abd. Majid; Zainol Abidin, Ibrahim (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org